Engineering of robust topological quantum phases in graphene nanoribbons - Gröning, Oliver; Wang, Shiyong; Yao, Xuelin; Pignedoli, Carlo A.; Borin Barin, Gabriela; Daniels, Colin; Cupo, Andrew; Meunier, Vincent; Feng, Xinliang; Narita, Akimitsu; Müllen, Klaus; Ruffieux, Pascal; et al. (Nature (London), 2018)
Boundaries between distinct topological phases of matter support robust, yet exotic quantum states such as spin–momentum locked transport channels or Majorana fermions 1 – 3 . The idea of using such states in spintronic devices or as qubits in quantum information technology is a strong driver of current research in condensed matter physics 4 – 6 . The topological properties of quantum states have helped to explain the conductivity of doped trans -polyacetylene in terms of dispersionless soliton states 7 – 9 . In their seminal paper, Su, Schrieffer and Heeger (SSH) described these exotic quantum states using a one-dimensional tight-binding model 10 , 11 . Because the SSH model describes chiral topological insulators, charge fractionalization and spin–charge separation in one dimension, numerous efforts have been made to realize the SSH Hamiltonian in cold-atom, photonic and acoustic experimental configurations 12 – 14 . It is, however, desirable to rationally engineer topological electronic phases into stable and processable materials to exploit the corresponding quantum states. Here we present a flexible strategy based on atomically precise graphene nanoribbons to design robust nanomaterials exhibiting the valence electronic structures described by the SSH Hamiltonian 15 – 17 . We demonstrate the controlled periodic coupling of topological boundary states 18 at junctions of graphene nanoribbons with armchair edges to create quasi-one-dimensional trivial and non-trivial electronic quantum phases. This strategy has the potential to tune the bandwidth of the topological electronic bands close to the energy scale of proximity-induced spin–orbit coupling 19 or superconductivity 20 , and may allow the realization of Kitaev-like Hamiltonians 3 and Majorana-type end states 21 . Graphene nanoribbons are used to design robust nanomaterials with controlled periodic coupling of topological boundary states to create quasi-one-dimensional trivial and non-trivial electronic quantum phases.